Pengaruh Promosi dan Harga terhadap Keputusan Konsumen Jasa Sewa Forklift pada PT Mahira Multi Sarana di Kabupaten Sidoarjo - Muhammad Muflih Sulaiman; Bambang Karnain; Rina Dewi; Sugiharto Sugiharto; Harsono Teguh Santoso (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
His research aims to investigate the influence of promotions and prices on consumer decisions in choosing forklift rental services at PT. Mahira Multi Sarana, Sidoarjo Regency. The research method used is a survey using a questionnaire as a data collection tool. The sample for this study consisted of consumers who had used the company's forklift rental services. The data analysis technique used is multiple linear regression to test the relationship between promotion and price variables on consumer decisions. The research results show that promotions and prices have a significant effect on consumers' decisions to use forklift rental services. The implication of this research is the importance of companies in designing effective promotional strategies and setting competitive prices to influence consumer decisions in choosing forklift rental services.